2014
DOI: 10.1080/01496395.2014.967411
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behavior and Mechanism of Humic Acid on Aminated Magnetic Nanoadsorbent

Abstract: Adsorptive removal of aqueous humic acid (HA) with aminopropyl functionalized silica coated Fe 3 O 4 nanoparticles was investigated. The adsorption isotherm of HA can be described very well by both the Langmuir and Freundlich models and the theoretical maximum adsorption capacity was 181.82 mg/g. Adsorption kinetics followed both the diffusion-controlled and the attachment-controlled process. HA adsorption increased monotonously with increasing solution pH. The presence of cations in solution, results in augme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 40 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Aqueous HA is removed with aminopropyl functionalized silica coated MNPs that show excellent desorption and regeneration properties. Zeta potential and XPS analysis reveal that electrostatic interaction and surface complexation between protonated amino groups and the disassociated HA molecules are the main adsorption mechanism [259]. Double functionalized magnetic NPs (DFMNPs) have been developed for extraction of BPA in an aqueous phase.…”
Section: Adsorptive and Separative Removal Of Organic Contaminantsmentioning
confidence: 99%
“…Aqueous HA is removed with aminopropyl functionalized silica coated MNPs that show excellent desorption and regeneration properties. Zeta potential and XPS analysis reveal that electrostatic interaction and surface complexation between protonated amino groups and the disassociated HA molecules are the main adsorption mechanism [259]. Double functionalized magnetic NPs (DFMNPs) have been developed for extraction of BPA in an aqueous phase.…”
Section: Adsorptive and Separative Removal Of Organic Contaminantsmentioning
confidence: 99%
“…It was demonstrated that the introduction of quaternary ammonium groups in adsorbents is beneficial for the adsorption of NOM, and increases their antibacterial activity. Therefore, considering rigid structures are helpful for the improvement of surface area, in this study, both rigid structures and quaternary ammonium groups were introduced during the preparation process to obtain a multifunctional β-CD-based polymer in the aqueous phase, which is expected to realize the simultaneous and rapid removal of NOM and OMPs and detrimental microorganisms from water.…”
Section: Introductionmentioning
confidence: 99%